2007
DOI: 10.1111/j.1472-765x.2007.02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of hepatitis A virus in urban sewage in Rio de Janeiro, Brazil

Abstract: Aims:  A one‐year survey was conducted to examine hepatitis A virus (HAV) prevalence, distribution of genotypes and their relationship to bacterial indicators in raw and treated sewage samples. Methods and Results:  Fifty sewage samples (raw = 25 and treated = 25) were collected twice monthly from one sewage treatment plant in Rio de Janeiro. Virus concentration was performed by adsorption to an electronegative membrane followed by ultrafiltration. Viral RNA was detected by nested reverse transcriptase‐polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 31 publications
(75 reference statements)
1
28
1
1
Order By: Relevance
“…This may be due to the nature of our samples, or it could be due to the qPCR assay used in this study, which could target two main types of HPyV (polyomaviruses JC and BK [JCPyV and BKPyV]), whereas the assay used in the previous study mainly targets JCPyV. Even though some studies have reported the presence of HAV in environmental water media (8,13,40,48), no HAV was detected in any of our biosolid samples. The occurrence of HAV indicates that the risk of transporting HAV from landapplied biosolids to the natural environment is minimal.…”
Section: Discussionmentioning
confidence: 39%
“…This may be due to the nature of our samples, or it could be due to the qPCR assay used in this study, which could target two main types of HPyV (polyomaviruses JC and BK [JCPyV and BKPyV]), whereas the assay used in the previous study mainly targets JCPyV. Even though some studies have reported the presence of HAV in environmental water media (8,13,40,48), no HAV was detected in any of our biosolid samples. The occurrence of HAV indicates that the risk of transporting HAV from landapplied biosolids to the natural environment is minimal.…”
Section: Discussionmentioning
confidence: 39%
“…Previous data published elsewhere using the same samples showed a detection of 92% of hepatitis A virus (HAV) using qPCR, and 32% and 16% for treated and untreated samples, respectively (Villar et al 2007). In another study, the percentage of norovirus detected ranged from 15% to 58%, depending on the methodology of detection used (Victoria et al in press).…”
Section: Resultsmentioning
confidence: 80%
“…One advantage of ultrafiltration procedures for water testing is that it can simultaneously concentrate multiple pathogen classes (virus, bacterium, parasite) Holowecky et al 2009;Morales-Morales et al 2003;Polaczyk et al 2008). Alternatively, ultrafiltration may be used as a secondary concentration step after the viral particles have been purified by another method (Brassard et al 2005;Divizia et al 1989;Villar et al 2007). Ultracentrifugation protocols have been developed for the extraction of HAV and NoV from soft fruits, meat and shellfish (Finance et al 1981;Rzezutka et al 2005;Rzezutka et al 2006;Sunen et al 2004).…”
Section: Sample Preparationmentioning
confidence: 99%